(untitled) (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT This classroom action research aimed to enhance students’ ethical behavior by integrating the Contextual Teaching and Learning (CTL) model with the local Hindu doctrine of Karmaphala—a fundamental belief in the law of cause and effect of actions. The study was conducted with 44 tenth-grade students of the Computer Network Engineering program at SMK Negeri Bali Mandara during the 2023/2024 academic year. Employing two research cycles, the study applied planning, implementation, observation/evaluation, and reflection stages. The CTL approach was designed to contextualize moral learning through real-life experiences using role-plays, case discussions, and reflective activities. Quantitative data were gathered through multiple-choice tests and student perception surveys, while qualitative data were collected via direct classroom observations. The findings from the first cycle showed only 60% of students reached the minimum passing grade, and only half showed disciplined and responsible behavior. Improvements were made in the second cycle, including the use of contextual media and interactive activities. The second cycle recorded a 90% success rate in knowledge assessment, with 80% of students positively responding to the learning process and 90% demonstrating moral discipline. These results indicate that the CTL model, when integrated with local cultural values such as Karmaphala, effectively fosters not only cognitive understanding but also the development of ethical character. The study concludes that such a culturally grounded approach is essential for enhancing moral education in schools. Keywords: Contextual Teaching and Learning, Karmaphala, character education, Hindu values, classroom action research